مفهوم الذات للقدرة الأكاديمية وعلاقته بالسلوك الفوضوي لدى تلاميذ مرحلة التعليم المتوسط - عزي, أحمد; مسعي أحمد, خالد (University of Eloued جامعة الوادي, 2021)
Abstract: The current study aims to identify the relationship between the selfconcept of academic ability and the chaotic behavior of middle school students, as well as revealing the differences between the sexes (males - females) in the degrees of learned helplessness in the two groups. To achieve the objectives of the study, we used the descriptive approach, through the application of the self-concept scale of academic ability of: (Brookover et Erickson), which Youssef Fattami translated and adapted to the Jordanian Arab environment, and the scale of chaotic behavior of Suhail Hassan Ahmed (2007) on a sample of (80) students. Choosing them at random from some of the averages in Bayadah and Robbah. The results of the study resulted in the following: - There is a negative correlation between the self-concept of academic ability and the chaotic behavior of middle school students. - There are no statistically significant differences in the degrees of self concept of academic ability among middle school students according to gender (males - females). - There are statistically significant differences in the degrees of chaotic behavior among middle school students according to gender (males - females), in favor of males. - There are no statistically significant differences between middle school students on the scale of chaotic behavior according to the academic level (second average / third average / fourth average). The results of the study were interpreted in the light of theoretical frameworks and previous studies, and this study came out with some proposals.
دراسة على عينة من التلاميذ ببعض متوسطات دائرتي البياضة والرباح
مذكرة ماستر في علم النفس تخصص علم النفس المدرسي
Keywords: الذات الأكاديمي، moi académique, Academic self; السلوك الفوضوي، comportement chaotique, Disruptive behavior